2007
DOI: 10.1002/jbm.b.30929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiance, wavelength, and thermal emission of different light curing units on the Knoop and Vickers hardness of a composite resin

Abstract: The aim of this study was to evaluate the effects of irradiance, light emission wavelength, and heating of different light curing units on the Knoop and Vickers hardness of a hybrid composite resin. The specimens were irradiated during 40 s with ten different light curing units, LEDs, and halogen lights. The spectral emission of each light curing unit was assessed by a spectrometer, the irradiance was measured by two commercial radiometers, and the heating measured with a thermocouple. After 48 h of storage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
2
27
1
Order By: Relevance
“…The lowest hardness and elastic modulus values were found on composite's bottom surface. Previous studies had also found similar results 12,21,24,25 . During photopolymerization, there is a considerable reduction of irradiance in deeper regions through the bulk of the composite, due to absorption and scattering of light by the resin matrix and particles filler 25 .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The lowest hardness and elastic modulus values were found on composite's bottom surface. Previous studies had also found similar results 12,21,24,25 . During photopolymerization, there is a considerable reduction of irradiance in deeper regions through the bulk of the composite, due to absorption and scattering of light by the resin matrix and particles filler 25 .…”
Section: Discussionsupporting
confidence: 78%
“…Since the energy density was kept constant for the three LED LCUs, we could suggest the influence of the light's wavelength on the results. Previous studies report that not only the irradiance but also the wavelength of the emitted light has a direct effect on the degree of polymerization of resin composites 12,21 . According to Nomoto 11 , the polymerization of composites is affected by light wavelength, 470 nm being the most efficient because it maximizes the camphorquinone activation 1,10,19 , which is the most commonly present photoinitiator in the composition of composites 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many parameters may affect the degree of polymerization of bulk fill RBCs such as their composition (photoinitiators, fillers and organic matrix) 6 , the technical characteristics of the light-curing unit (light intensity, thermal emission, wave length range, diameter of the tip) and the conditions of photo-polymerization (curing mode and exposure time) 22 , the post-irradiation period 21 , the temperature 23,24 and the incremental thickness of the material 25 . As statistical analysis revealed the existence of significant differences among the tested bulk fill RBCs with regard to microhardness, the formulated Ho1, which states that there were no differences in microhardness among the RBC materials of the same measurement depth, had to be rejected.…”
Section: Discussionmentioning
confidence: 99%